Back Cover: Bioinduced Room‐Temperature Methanol Reforming (Angew. Chem. Int. Ed. 35/2015). Issue 35 (29th July 2015) - Heim, Leo E.; Thiel, Daniel; Gedig, Christian; Deska, Jan; Prechtl, Martin H. G.
<x xml:space="preserve">Abstract</x> The best of two worlds is exploited when methanol‐oxidizing enzymes are combined with formaldehyde‐reforming metal complexes. In their Communication on page 10308 ff., J. Deska, M. Prechtl et al. employ an organometallic formaldehyde dehydrogenase mimic to construct a methylotrophic in vitro metabolism. The interplay of biocatalytic MeOH activation with the transition‐metal‐catalyzed dehydrogenation provides a room‐temperature path for the liberation of hydrogen gas from aqueous methanol.